Adolescents’ judgments of a refusal statement in Malayalam: A metapragmatic approach to conversation analysis of children with Specific Learning Disability - Geethi S. Shyamala K. Chengappaa (Journal of All India Institute of Speech and Hearing)
A group of children with Speci c Learning Disability (SLD) ranging from 12;0 - 14;11 years were compared against a group of age matched typically developing children while investigating their metapragmatic skills. Children’s verbal judgements of an expression of refusal statement in a conversational act were used for this purpose. Findings revealed a developmental progression in children’s metapragmatic awareness during the adolescent ages. The results also indicated that children with SLD performed less well than typical children. This di erence may be probably attributed to these children’s poor language processing skills especially with regard to their choice of words, speech acts and impairments in social perception.